Den norske videobutikken: 1979–2017 - Øfsti, Marius (Nordlit, 2019)
De første norske videobutikkene åpnet dørene i 1979 og de siste stengte i 2017. I løpet av denne tidsperioden rakk de å bryte NRKs monopol på film og tv-serier i hjemmet, de ble utskjelt, de ble en av de viktigste kulturinstitusjonene i landet og de tilbød et relativt stort utvalg i film. Ved å studere bransjeblader, annonser, lokalaviser og kommunale arkiver tegner denne artikkelen et bilde av de norske videobutikkenes historie på nasjonalt plan og utdyper dette med en lokal case.The first Norwegian video-stores opened its doors in 1979 and the last ones closed in 2017. During this time, they were the first to break the state monopoly on filmed home entertainment. The video-stores became notorious, but they also established themselves as some of the most important cultural institutions in the country, with a relatively wide selection of films to offer customers. By studying trade magazines, advertisements, local newspapers and local council archives, this article traces the history of the Norwegian video-stores on a national level and, through the use of one case example, on a local level.
Keywords: Videobutikker; mediehistorie; filmhistorie; Steinkjer; medieøkonomi